Dual index production and subcontracting policies for assemble-to-order systems. Issue 5 (3rd May 2016) - Sinha, Ashesh Kumar; Krishnamurthy, Ananth
ABSTRACT: We analyze tradeoffs related to production and subcontracting decisions in an assemble-to-order system with capacity constraints and stochastic lead times. We assume that component replenishment is carried out by orders to a subcontractor and component stock levels at the manufacturer are determined by dual index-based policies. Furthermore, customer demands for the final product are immediately satisfied if all of the required components are in stock; otherwise, they are back-ordered. In order to maintain high service levels, the manufacturer reserves the option to produce components internally. Using queuing models, we analyze the tradeoffs related to internal manufacturing versus subcontracting under different types of dual index policies. We use Matrix-Geometric methods to conduct an exact analysis for an assemble-to-order system with two components and develop a decomposition-based algorithm to analyze the performance of systems with more than two products. Numerical studies provide useful insights on the performance of the various dual index policies under study.